Open Science - NOVA CRIS group (2024)
NOVA University Lisbon is committed to advancing science and the wide spread dissemination of knowledge for the benefit of society, through the adoption of open, equitable, reproducible, and responsible research practices. NOVA recognizes Open Science as a guiding paradigm and aims to promote it by supporting research processes and tools that lead to transparency, integrity, collaboration, inclusivity, and sustainability; promoting new working methods and new social partnerships; encouraging the free dissemination of knowledge and the accessibility and reuse of research results, stimulating open access to publications and data; supporting open participation and dialogue with civil society and other knowledge systems; and building the necessary infrastructures, skills, and incentives for Open Science. This guide is aimed at researchers across all disciplines from NOVA University Lisbon, providing support through each stage of their research process, offering tools and practices in each chapter.